Systemic lupus erythematosus masquerading as ulcerative colitis: a clinical case of lupus enteritis - Ilkana Guliyeva; Fidan Gasimova; Gulnara Nur-Mammadova; Nargiz Guseynova; Magrur Mammadov; Nijat Bayimov (Caucasian Medical Journal, 2026)
Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease with a wide range of clinical features. Involvement of the gastrointestinal tract (GIT), especially in the form of lupus enteritis, can imitate inflammatory bowel disease (IBD), making diagnosis difficult. We present the case of a young woman with previously diagnosed ulcerative colitis, who subsequently showed immunological and clinical signs of SLE with the development of lupus enteritis. This case highlights the need for a comprehensive immunological examination for atypical IBD and the importance of differential diagnosis between SLE and IBD.